Victory above all: the weight loss practices and perceptions of Chinese male kickboxers - Fanjie Meng; Yuming Zhong; Zhao Zhang; Zihan Ren (PeerJ)
Objectives Kickboxing is a dynamic combat sport (CS) in which two competitors engage in full-force strikes using their hands, elbows, knees, shins, and feet. To ensure athletes compete against opponents of similar body size and weight for fairness, kickboxing competition is classified according to weight classes. Previous studies revealed that CS athletes tend to intentionally lose weight to gain a competitive advantage over their opponents. However, little is known about weight loss (WL) practices in kickboxers and the perceptions of CS athletes about WL. The aim of this study is to investigate the WL practices and perceptions of Chinese male kickboxers. Methods A total of 152 Chinese male kickboxers completed the adapted Rapid WL Questionnaire. Participants were categorized by age group, weight category, competitive level, attitude toward impact of WL on health, and performance. Results Sixty-eight percent of kickboxers purposefully engaged in WL practices. The average habitual WL was 6.0% of body mass (BM), with the average highest WL being 8.8% of BM. Most participants reduced 41–60% of their total planned magnitude of WL between 60 days and 9 days before the weigh-in, 21–40% between 8 days and 2 days before the weigh-in, and 0–20% within 1 day before the weigh-in. Coaches (67%) were most reported as the primary guides for WL. The primary reason kickboxers engage in WL is competing against lighter opponents to increase the chances of winning (70%). Most participants believed that WL had no impact on health (42%), improved performance (57%), and did not lead to unfair competition (73%). Significant differences were observed in both the highest WL% (p = 0.005, p = 0.018), the habitual WL% (p = 0.005, p = 0.018), the age beginning WL (p = 0.005, p = 0.018), and the annual WL times (p = 0.005, p = 0.018) across age and competitive level, but not observed across weight category, and attitudes toward both the health and performance impacts of WL (all p > 0.05). No significant differences were found in habitual weight regain after weigh-in/habitual WL (%) after weigh-in across all groups (all p > 0.05). Conclusions The prevalence of WL among Chinese male kickboxers is relatively low when compared to other CS, but the magnitude is relatively higher compared with previous studies. Their WL practices are mainly guided by kickboxing coach, and the primary reasons of WL is to gain a competitive advantage and improve performance.